Irrigation System Descriptions for Tropical and Subtropical Fruit Crops in Florida - Jonathan Henry Crane; Haimanote Bayabil; Edward A. Evans; Fredy Ballen (EDIS, 2020)
Florida's tropical and subtropical fruit crop industries use various irrigation systems, including high-volume systems designed for irrigation and freeze protection, drip systems for herbaceous fruit crops (papaya, banana), and microsprinkler types, mainly for irrigation and fertigation. There continues to be a steady stream of potential tropical and subtropical fruit producers in Florida, many with little to no knowledge of the various types or purposes of various irrigation system that have been used successfully for the past 60 years. This new 9-page publication of the UF/IFAS Horticultural Sciences Department includes potential producers, Extension faculty and agents, and irrigation companies. Written by Jonathan Crane, Haimanote Bayabil, Edward A. Evans, and Fredy Ballen. https://edis.ifas.ufl.edu/hs1375